The value of intravascular ultrasound in patients with acute myocardial infarction - Cîrjan Alexandru Petrinel; Kulcsar Iulia Daniela; Stavaru Radu; Catana Nicu; Deleanu Dan; Predescu Lucian Marius (Romanian Journal of Cardiology, 2022)
Defining the best percutaneous coronary intervention (PCI) in acute myocardial infarction is sometimes difficult, bearing in mind that time is of the essence in preventing myocardial tissue damage. There are invasive modalities to determine the best strategy. These include intravascular ultrasound (IVUS) and optical coherence tomography (OCT), methods that could underline plaque rupture, thrombus, positive remodeling, greater plaque burden, and tissue prolapse. Virtual histology IVUS is capable of detecting lesions containing large necrotic cores and thin cap fibroatheroma (independent predictors of no-reflow in acute myocardial patients). Using these imagistic modalities can lead the PCI strategy in order to obtain the best possible outcome of the procedure for the patient.